Pengembangan Aplikasi Reservasi dan Manajemen Marketplace Homestay berbasis Web (Studi Kasus: Kota Pekanbaru) - Habib Yafi Ardi; Bayu Priyambadha; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In Riau Province, Pekanbaru City, in the accommodation category of housing rentals in 2012, experiencing rapid development due to the impact of the 2012 Pekan Olahraga Nasional (PON), communities competed to build properties such as hotels, homestays, boarding houses, condominiums, and guesthouses to meet the needs of migrants from outside Riau province. But in 2013 the use of these properties changed over from previously intended athletes, organizers, and spectators outside of the province which became massive people who wanted to work in Pekanbaru. So that small properties such as homestays and boarding houses are unable to compete with hotels that already have their own markets. Based on the problems that have been formulated above, a web-based software is developed, namely Homie. The purpose of this software is to create a market for the owners of residential rental properties where owners and customers of residential tenants can be reunited. From the results of this study twenty-two functional requirements and one non-functional requirement were obtained from the needs analysis stage, then architectural design, component design, database design, and interface design used to generate system implementation. Then in the testing phase the results of three unit tests, one integration test, and twenty-four validation tests that provide a 100% valid value are obtained. Then on compatibility testing the results are that Homie applications can run on 8 types of browsers including edge, firefox, safari, google chrome, iOS devices, and android devices.